Effect of bulking materials over the composting of bio-slurry - Al-Amin, M; Rahman, MM; Islam, SMA; Dhakal, H; Khan, MRI; Amin, MR; Kabir, AKMA (Bangladesh Journal of Animal Science, 2021)
Bio-slurry is considered as a good quality organic fertilizer in Bangladesh agriculture. An experiment was conducted at Bangladesh Agricultural University, Mymensingh to assess the effect of bulking materials over the composting of bio-slurry. The experiment was conducted with 4 treatments each of 3 replications. The treatments for compost preparation were, T0 (50% Bio-slurry + 50% manure), T1 (50% Bio-slurry + 50% manure and saw dust), T2 (50% Bio-slurry + 50% manure and rice straw), T3 (50% Bio-slurry + 50% manure and tree leaves). Compost moisture, pH, temperature and C: N ratio was assessed every week. Maximum temperature found in T1 (34.030C) and other treatments showed a slower rise in temperature. Highest C:N ratio (19.30) was obtained in T3. The pH of the compost was significantly influenced by saw dust which ranged from 8.28 in T2 to 8.74 in T1. Moisture content of compost was significantly influenced by bulky materials and ranged from 56.34 to 68.83. At 42 day the highest crude fiber was obtained in T2 (25.16%). The results suggest that bulky materials treated bio-slurry can be good compost which will be very effective to soil and crops. Bang. J. Anim. Sci. 2020. 49 (2): 142-150